Effect of seasonality and Cr(VI) on starch-sucrose partitioning and related enzymes in floating leaves of Salvinia minima - Rosa, Mariana (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2017 Elsevier Masson SAS. All rights reserved.